Towards a sociology of selfies : the filtered face - Cambre, Maria-Carolina; Lavrence, Christine (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book examines selfies as a relational and processual networked social practice, performed between people within digital contexts and that involve online/offline intersections and tensions. It offers an analysis of selfies through a rich and interdisciplinary framework, that explores the ritualized and affective engagements selfies provoke from others. Given that selfies by definition are shared and posted through networked platforms, they complicate notions of traditional photographic self-portraiture. As such, this book explores how selfies invoke broader, stratified patterns of looking that are occluded in discourses of "empowerment" and "visibility", as well as the subjectivities these networked practices work to produce. Drawing on extensive qualitative research conducted over a period of three years, this book questions not only what selfies are but what they do, the worlds they create, the imaginaries that organize them, and the flows of desire, affect and normativity that underpin them, questions that can only be addressed through research that closely attends to the experience of selfie-takers. It will be of interest to those working in the fields of Sociology, Cultural studies, Communications, Visual Studies, Social Media studies, Feminist research and Affect Theory"--
Keywords: Selfies (Photography) -- Psychological aspects; Internet users -- Psychology; Social psychology; Online identities; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General